Agave sisalana extract induces cell death in Aedes aegypti hemocytes increasing nitric oxide production - Louise Helena Guimarães de Oliveira; Patricia Alexandria Paiva Silva de Sousa; Fabrine Felipe Hilario; Gabriel Joventino Nascimento; João Paulo Saraiva Morais; Everaldo Paulo de Medeiros; Manoel Francisco de Sousa; Fabiola da Cruz Nunes (Asian Pacific Journal of Tropical Biomedicine, 2016)
Objective: To investigate the effects of Agave sisalana (A. sisalana) extract on Aedes aegypti (Ae. aegypti) primary cell culture. Methods: Cells of Ae. aegypti were exposed to different concentrations of A. sisalana crude extract (0.18–6.00 mg/mL) for 24 h. Then, the cells were labeled with propidium iodide and subjected to fluorescence microscopy to verify cell viability. In addition, nitric oxide production was measured. Results: Results showed that cells exposed to 6 mg/mL of the crude extract presented a greater percentage of death when compared to control (73.8% ± 9.6% vs. 34.6% ± 9.6%). Furthermore, there was an increase in the nitric oxide production in cells exposed to 6 mg/mL of A. sisalana crude extract [(0.81 ± 0.08) μmol/L] compared to control group [(0.41 ± 0.18) μmol/L]. Conclusions: The results show that A. sisalana is cytotoxic to Ae. aegypti and may be used as raw material for new eco-friendly and inexpensive insecticides, since sisal industry discards the liquid waste for the extraction of plant fiber.